Identity, education, gender and nation. A Galiza imaxinada through the Galician emigration press (1915-1936) - Bolaño Amigo, María Eugenia (Historia y Memoria de la Educación, 2020)
This work examines the representations of the Galiza imaxinada – Galicia imagined - that, through texts and images related to education and childhood, are portrayed by the press produced by Galician emigrants. For this purpose, we analyze the content of a sample that includes all the numbers published between 1915 and 1936 of Céltiga (Buenos Aires, Argentina) and Eco de Galicia (La Habana, Cuba), magazines that specifically address the representations of identity that go beyond the notions of gender, social class and nation.